PENGARUH GAME FREE FIRE TERHADAP PERILAKU SOSIAL SISWA DI SDN 3 TANGKILING DESA SUKAMULYA, KECAMATAN BUKIT BATU KOTA PALANGKA RAYA - ButarButar, Tiara; Dotrimensi, Dotrimensi; Triyani, Triyani (Bhinneka Multidisiplin Journal, 2024)
This research aims to determine the effect of the free fire game on students' social behavior at SDN 3 Tangkiling, Sukamulya Village, Tangkiling, Bukit Batu District, Palangka Raya City. This online game affects students' social behavior and disrupts learning activities both at home and at school. These include students being lazy about studying, not concentrating, not sleeping enough, and being lazy about doing other activities. This study used a quantitative approach. The sample studied was 30 students of grades IV, V, VI SD Negeri 3 Kota Tangkiling. Data collection techniques using questionnaires. The data obtained were analyzed using data analysis techniques consisting of normality tests, homogeneity tests, linear regression tests, validity tests and reliability tests. After that the data is used using hypothesis tests including f- test and t-test. Based on the results of research conducted by the t-test, the calculated t value = 8.905 is greater than the table t value = 2.048, at a significance level of 5%. This shows a significant influence of variable X on variable Y. So it can be concluded that there is a negative and significant influence of online games on student behavior at SDN 3 Tangkiling, Sukamulya Village, Tangkiling, Bukit Batu District, Palangka Raya City